Acidified drinking water attenuates motor deficits and brain pathology in a mouse model of a childhood neurodegenerative disorder - Attila D. Kovács; Logan M. Langin; Jose L. Gonzalez Hernandez; David A. Pearce (Scientific Reports, 2022)
Abstract We recently demonstrated that HCl-acidified drinking water, which is widely used in laboratory animal facilities, had some beneficial effects in the Cln3 −/− mouse model of juvenile Batten disease, a neurodegenerative lysosomal storage disorder1. Here we tested if acidified drinking water has therapeutic effects in Cln1 R151X nonsense mutant mice, a model of the infantile form of Batten disease. In Cln1 R151X mice, acidified drinking water received from weaning prevented the impairment in pole climbing ability measured at 3 and 6 months of age. Histopathological analysis of the brain at 6 months showed that acidified drinking water decreased the amount of lysosomal storage material, reduced astrocytosis in the striatum and somatosensory barrelfield cortex, and attenuated microglial activation in the thalamus. Compared to wild-type mice, the gut microbiota of Cln1 R151X mice was markedly different. Acidified drinking water significantly altered the gut microbiota composition of Cln1 R151X mice, indicating a contribution of gut bacteria to the therapeutic effects of acidified water. Our results in Cln1 R151X mice suggest that acidified drinking water may have beneficial effects for patients with infantile Batten disease. This study also verifies that acidified drinking water can modify disease phenotypes in mouse models, contributing to the inter-laboratory variations in neurological and pathological findings.